BAHASA INDONESIA PEMANFAATAN MEDIA SOSIAL MELALUI TIKTOK SHOP UNTUK PENINGKATAN PENJUALAN BAGI PELAKU USAHA DI VIRAGEAWIE - Andre Suryaningprang; Fanji Wijaya; Ridlwan Muttaqin; Rizki Surya Tawaqal; Arie Hendra Saputro (Universitas Mataram, 2023)
The problem that occurs is that partners have not fully utilized social media as a tool to increase sales. Partners are still focusing on the conventional production of goods and services. Forms of promotions and campaigns on social media have been carried out but have not utilized other features that have a higher level of marketing. Social media plays an important role in disseminating the market. Partners should utilize and optimize social media to market their products. Tiktok shop is a marketing tool that can help partners increase sales. This Community Service aims to assist, provide training and provide tutorials in the use of social media. Another goal is to create social media content for Virageawie partners to increase product sales. This Community Service is carried out for 1 (one) week involving 1 (one) Partner, namely Virageawie with a total of 5 (five) HR people. The solution offered in this service program is to pay attention to registering, managing, accompanying and using the Tiktok shop as a marketing tool. Social media has a very large role and gives quite a big influence in terms of marketing level. Utilizing social media can make it easier for partners to increase sales, considering that social media is a marketing tool that can be seen and reached by many people. By paying attention to the various advantages and benefits of the community service team, the community service team plans to carry out community service activities. Based on the partner problems described above, the solutions that can be given are; (1) Providing socialization on the importance of social media to increase sales, (2) Providing assistance in creating tiktok and tiktok shop accounts, (3) Providing training related to content creation, effective communication and handling consumers, (4) Providing evaluation of activities community service. Business development needs to understand consumer consumption patterns and consumer behavior. Digital and social commerce trends also influence consumer behavior. By understanding and following digital developments, business people can continue to survive and develop their business. One that can be used and empowered in this digital era is to utilize social media, especially the Tiktok shop.